Pengaruh Brand Image, Kualitas Produk, dan Label Halal terhadap Keputusan Pembelian pada Produk Skincare Avoskin di Kota Yogyakarta - Berliany, Fany Aulia; Prasetyo, Heri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The increasing competitiveness in Indonesia’s skincare industry demands that local brands, including Avoskin, strengthen consumer trust through various factors such as brand image, product quality, and halal certification. Despite Avoskin’s strong market presence, recent sales data show it lags behind other local competitors, indicating a critical issue in consumer purchase decisions. This study aims to examine the influence of brand image, product quality, and halal labels on the purchase decisions of Avoskin skincare consumers in Yogyakarta. A quantitative approach was employed using purposive sampling, with 100 respondents who have purchased and used Avoskin products. Data were collected via an online questionnaire and analyzed through multiple linear regression using SPSS version 23. The results indicate that brand image, product quality, and halal labels each have a significant and positive influence on purchase decisions both partially and simultaneously. The coefficient of determination (Adjusted R²) shows that these three factors collectively explain 82% of the variation in purchase decisions. Among these variables, product quality holds the strongest influence, followed by the halal label and brand image. This finding highlights that enhancing product quality and maintaining consumer trust through a strong brand image and credible halal certification are essential strategies for improving purchasing decisions. The research provides empirical evidence for skincare businesses aiming to strengthen consumer loyalty in a highly competitive market.